PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERINTEGRASI PENDEKATAN CULTURALLY RESPONSIVE TEACHING TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS VI SD - Wahidatul Aulawy; Mei Fita Asri Untari; Ipnu Pramono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to examine the application of the Problem Based Learning learning model which is integrated with the Culturally Responsive Teaching approach to the learning outcomes of class VI elementary school students. Combination research with a sequential exploratory design research method, data collection begins with qualitative data then continues with quantitative data collection. The results of the research show that the application of the CRT integrated PBL model has an effect on Indonesian language learning outcomes regarding facts and opinions, obtaining a percentage of learning implementation observation results of 88.6% in the very good category, t test analysis with a significance level of 0.000>0.05, N-Gain test The result was 0.738 in the high category and there was a significant increase between the pretest and posttest (45.65 < 84.57) indicating that students understood the material better.